Evaluation of Cluster Frontline Demonstration on Urd for Enhancing Productivity - Saravanakumar, S.; Premalatha, A.; Prabakaran, D. John; Thirumoorthi, M. (Indian Journal of Extension Education, 2020)
Urd or Black gram (Vigna mungo L.) is an important pulse crop cultivated in Erode district of Tamil Nadu but due to improper adoption of improved technologies the productivity is far below (680 kg/ha) against the average productivity of the state (861 kg/ha). Attempts were made to improve the productivity of black gram through KVK, Myrada and conducted cluster frontline demonstration with improved production technologies in 25 farmers’ field during rabi 2019-2020. The improved production technologies comprising of high yielding variety namely Vamban 6 (VBN 6), seed treatment with bio-fertilizers and bio agents, integrated pest management technologies and foliar application of micronutrients. By adopting these technologies, the farmers harvested an average yield of 7.79 q/ha with a yield advantage of 19.85 per cent over the farmer practices. The improved practices gave higher net return of Rs. 23134.5/ha and benefit cost ratio of 2.03 where as benefit cost ratio of 1.65 was observed in farmer practices. The average extension gap, technology gap and technology index were 1.29 q/ha, 0.79 q/ha, and 8.35 per cent respectively. The results indicated that, adoption of improved production technologies minimizes the yield gap and provided higher return to the farming community.
Keywords: Cluster demonstration; Economics; Yield; Urd